Construction and Application of Dynamic Credit Evaluation Model for Mobile User - Lingyan Bian (Dianxin kexue)
Combined with the data analysis of mobile users' characteristics, a scientific and dynamic estimation models for user credit were built. It can be applied to different solutions of suspended service for different mobile users based on the diverse credit category. It is effective to improve user experience, strengthen user loyalty, exploit potential spending power and ultimately increase the operating income.